Way of scoring by Spanish First Division volleyball teams in relation to winning/losing, home/away, final classification, and type of confrontation - Palao, J.M.; Manzanares, P.; Valadés, D. (Journal of Human Sport & Exercise, 2015)
The aim of this study was to assess the way volleyball teams score with regard to: whether or not they won the game, whether they were the home or away team, the level of the opposing teams, and the type of confrontation. The sample was composed of 118,083 plays from 794 men`s volleyball matches and 125,751 plays from 719 women`s matches of Spain`s first division clubs (from the 2002-2003 season to the 2006-2007 season). The variables studied were: the way points were obtained in each play, being the home or away team, the level of the teams, the result of the match, and the type of confrontation between the teams with regard to their level. The results demonstrate that for both men`s and women`s teams, the majority of the points were obtained in attack and by opponent errors. Differences were found with regard to the way points were obtained when winning or losing the match was taken into account as well as when considering the level of the teams. This paper discusses the differences found with regard to whether the team is home or visiting and the type of confrontation.